Nurses' Responsibility for Independent Practice in Providing Nursing Care; A Study of Law Number 17 Of 2023 Concerning Health - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (CV. Inara, 2025)
Health is a fundamental right of every person in the world. To be healthy, health services are necessary. These health services are provided by health workers, one of which is nurses. The practice allows nurses to work independently outside hospitals and/or community health centres. This study aims to analyse the regulations and responsibilities of nurses who practise independently in providing nursing care as part of health services, as stipulated in Law Number 17 of 2023 concerning Health. The method used in this paper is a normative juridical method with a conceptual and regulatory approach. The data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The analysis was conducted qualitatively. The research findings show that Law Number 17 of 2023 concerning Health regulates legal relationships in the provision of health services differently from the old regulations. Within this framework, the analysis shows that it is necessary to provide clear regulations on nursing care activities carried out by independent nurses, particularly those related to the responsibilities that independent nurses must fulfil.